Moznosti vyuzití techniky autotransfúze v podmínkách dĕtské kardiochirurgie - Hájek, T; Kucera, V; Horváth, P; Slavík, Z; Kostelka, M; Hucín, B; Honĕk, T (Rozhledy v chirurgii, 1990)
Consequential miniaturization of the apparatus for extracorporeal circulation and its simple connection, by introduction of haemodilution into perfusion technique along with careful surgical technique and the introduction of the principle of autotransfusion made it possible to reduce the consumption of donor blood in our department during the last six years to 25%. Autotransfusion proved to be in children weighing more than 15 kg a safe method. In the first half of 1989 we made 194 operations of the open heart. 167 patients (i.e. 86%) of this number did not require preserved blood in the primary filling of the apparatus for extracorporeal circulation. In a group of 100 patients weighing more than 15 kg in 65% the method of autotransfusion was applied; 55% of the patients did not need donor blood in the course of hospitalization.
Keywords: kojenec; Infant; autologní krevní transfuze; Child; Cardiac Surgical Procedures; předškolní dítě; dítě; Blood Transfusion, Autologous; mimotělní oběh; Child, Preschool; lidé; kardiochirurgické výkony; Extracorporeal Circulation; Humans